Pemenuhan Kebutuhan Hierarki Abraham Maslow dalam Dinamika Keluarga: Analisis Film “Keluarga Cemara2” - Reski Reski; Irma Satriani (Linguistik : Jurnal Bahasa dan Sastra, 2025)
This article presents an analysis of the fulfillment of Abraham Maslow's hierarchical needs in the family dynamics shown in the film "Family Cemara". This research aims to identify how the characters in the film fulfill Maslow's five levels of needs, namely physiological needs, security, affection, self-esteem and self-actualization. The method used is a qualitative approach with narrative analysis of interactions between family members. The research results show that this film depicts the importance of emotional and social support in meeting basic needs and how relationships between family members contribute to well-being and harmony. In the context of the film, it can be seen that despite facing various challenges and difficulties, the Cemara family is still able to maintain solidarity and support each other. These findings provide insight into the relevance of Maslow's theory in the context of family life and highlight the important role of communication and solidarity in building healthy family dynamics. Apart from that, this article also discusses the implications of fulfilling these needs for individual and collective development in the family, as well as how values transmitted through daily interactions can shape the character and identity of family members. Thus, this research not only enriches filmography studies but also contributes to the understanding of family psychology in the context of Indonesian culture